PCR optimization for the detection of bunchy top virus of abaca (Musa textilis Nee) in Eastern Visayas Philippines - Mati-om, Jofil A.; Mati-om, Meriam B.; Piamonte, Robelyn T. (Annals of Tropical Research, 2022)
The bunchy top virus in Eastern Visayas has serverly reduced abaca production. Early and accurate detection of plant viral pathogens is an essential and crucial component for disease management. At present, there are no standard PCR conditions in the Eastern Visayas region for detecting the bunchy top virus at an early stage using PCR. Thus, optimization for the detection was carried out to assist in disease management. Different annealing temperatures (57, 60 and 65oC), gel concentrations (1, 1.5 and 2%), and running conditions (80, 90 and 100 volts) were tested using My TaqTM DNA Polymerase (Bioline, USA). The annealing temperatures of 57oC and 60oC resulted in DNA amplification as indicated by the presence of bands but absence of bands at 65oC. The higher voltages of 90 and 100 volts resulted in smears and distorted DNA bands with 1% and 1.5% agarose; thus 2% agarose gel was used to resolve small DNA fragments (100bp to 3kb). Electrophoresis using 80 volts for 45min successfully separated the DNA bands. The amplification of the product with internal control primers indicated the absence of PCR inhibitors in the abaca-extracted DNA samples. This confirmed the negative PCR reaction as indicative of the absence of the virus. The optimized PCR conditions could be applied by students and researchers for the early detection of bunchy top virus in the National Abaca Research Center Germplasm collection and the region.